Ghost wars the secret history of the CIA, Afghanistan, and bin Laden, from the Soviet invasion to September 10, 2001 - Coll, Steve (Penguin Books, 2005)
To what extent did America's best intelligence analysts grasp the rising threat of Islamist radicalism? Who tried to stop bin Laden and why did they fail? Comprehensively and for the first time, Pulitzer Prize-winning journalist Steve Coll recounts the history of the covert wars in Afghanistan that fueled Islamic militancy and sowed the seeds of the September 11 attacks. Based on scrupulous research and firsthand accounts by key government, intelligence, and military personnel both foreign and American, Coll details the secret history of the CIA's role in Afghanistan, the rise of the Taliban, the emergence of bin Laden, and the failed efforts by U.S. forces to find and assassinate bin Laden in Afghanistan.